2016
DOI: 10.1111/bph.13658
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Zn2+ and febrile seizure susceptibility

Abstract: Zn , the second most prevalent trace element in the body, is essential for supporting a wide range of biological functions. While the majority of Zn in the brain is protein-bound, a significant proportion of free Zn is found co-localized with glutamate in synaptic vesicles and is released in an activity-dependent manner. Clinical studies have shown Zn levels are significantly lower in blood and cerebrospinal fluid of children that suffer febrile seizures. Likewise, investigations in multiple animal models demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In particular, ZnR/GPR39 activity enhanced neuronal inhibitory tone. Zinc deficiency has been linked to epilepsy and seizures, which suggests an important physiological role for ZnR/GPR39 [ 38 , 39 , 40 ]. This specific extracellular receptor has been strongly linked to the regulation of the mitogen-activated protein kinase (MAPK) and PI3K pathways [ 41 , 42 , 43 , 44 ].…”
Section: Friendmentioning
confidence: 99%
“…In particular, ZnR/GPR39 activity enhanced neuronal inhibitory tone. Zinc deficiency has been linked to epilepsy and seizures, which suggests an important physiological role for ZnR/GPR39 [ 38 , 39 , 40 ]. This specific extracellular receptor has been strongly linked to the regulation of the mitogen-activated protein kinase (MAPK) and PI3K pathways [ 41 , 42 , 43 , 44 ].…”
Section: Friendmentioning
confidence: 99%
“…Similar ZnR/GPR39 responses were observed in postsynaptic neurons of the auditory brainstem nucleus, the dorsal cochlear nucleus [ 63 ]. Importantly, ZnR/GPR39 activity was shown to enhance neuronal inhibitory tone, and zinc deficiency is associated with epilepsy and seizures, suggesting the significant physiological role of ZnR/GPR39 [ 53 , 64 , 65 , 66 , 67 , 68 ]. Luminal application of Zn 2+ to colon epithelial cells, colonocytes, was sufficient to activate the plasma membrane ZnR/GPR39 [ 69 ], which is highly expressed in this tissue [ 70 , 71 ].…”
Section: Identification Of a Zn 2+ -Sensing Recmentioning
confidence: 99%
“…Recently, studies have shown that human mutations that alter zinc affinity on NR2A-containing NMDA receptors are associated with childhood epilepsies and cognitive deficits [ 60 ]. Decreased Zn 2+ serum levels have also been linked to febrile seizures in both humans and animal models [ 61 ]. In the context that enhanced extracellular citrate is convulsive [ 51 ], it seems likely that reduced zinc levels through citrate chelation are a mechanism that could at least partially contribute to excitation–inhibition imbalance and seizure susceptibility.…”
Section: The Zinc Chelation Hypothesis: a Mechanism Linking High mentioning
confidence: 99%
“…Citrate chelation of free zinc reduces the availability of zinc for the NMDA receptor, relieving the negative allosteric effect of zinc on NMDA receptor function, thereby increasing calcium flux through the NMDA receptor (note larger arrow indicating enhanced flux of calcium through the NMDA receptor). Schematics in A and B were motivated from [ 30 , 61 ]; ( C ) kinetic model simulations [ 55 , 62 ] of NMDA receptor currents generated by a 5 s pulse of glutamate under normal conditions (i.e., with free zinc) and under conditions in which extracellular citrate has chelated free zinc (i.e., without free zinc). Citrate chelation induces a larger and more sustained NMDA receptor current; ( D ) response of the kinetic model to six synaptic-like 1-ms pulses of glutamate, simulating a burst of gluatmatergic synaptic activity.…”
Section: Figurementioning
confidence: 99%